New crops from old computers [refurbished computers, Uganda] - Karamagi, Ednah (Technical Centre for Agricultural and Rural Cooperation, 2007)
Farmers in Uganda can now learn new skills and increase their incomes. A project using old computers has given rural communities Internet access and the opportunity to take part in e-learning programmes